Effects of exercise on neuromuscular junction components across age: Systematic review of animal experimental studies Neuroscience - Krause Neto, Walter; Ciena, Adriano Polican [UNESP]; Anaruma, Carlos Alberto [UNESP]; De Souza, Romeu Rodrigues; Gama, Eliane Florencio (Springer Nature, 2015)
Background: During almost one-third of our life, maturation of the nervous system promotes strength and muscle mass increase. However, as age advances, the nervous system begins to suffer a slow and continue reduction of its functions. Neuromuscular junction (NMJ) is one of the structures of which change due to aging process. Physical training leads to significant adjustments in NMJs of young and aged animals. Nevertheless, studies that aimed to investigate this effect have, in many cases, methodological variables that may have some influence on the result. Thus, this study aimed to carry out a systematic review about the effects of exercise training on the NMJ compartments of young, adult and aged animals. Results: We searched PubMed, Google Scholar, Science Direct, Scielo and Lilacs databases for animal experimental studies that studied exercise effects on the NMJs components across age. After inclusion and exclusion criteria, we included nine articles in systematic review and two for meta-analysis (young/adult NMJ). Conclusions: We identified that exercise training cause NMJ hypertrophy on young animals and NMJ compression on aged ones. However, many methodological issues such as age, skeletal muscle and fibers type, and type of exercise and training protocol might influence the results.
Keywords: Aerobic training; Myofibers; Myoneural junction; Strength training